Diversity of bioactive compounds from Parmotrema xanthinum as antimicrobial potential through in-vitro and in-silico assessment - OKY KUSUMA ATNI; ERMAN MUNIR; NURSAHARA PASARIBU (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Atni OK, Munir E, Pasaribu N. 2024. Diversity of bioactive compounds from Parmotrema xanthinum as antimicrobial potential through in-vitro and in-silico assessment. Biodiversitas 25: 4438-4449. Lichens, integral to ecosystem diversity, are known for producing bioactive secondary metabolites with significant pharmacological applications, particularly in antimicrobial therapies. This study evaluates the antimicrobial potential of Parmotrema xanthinum through in vitro and in silico approaches, emphasizing its role in biodiversity and drug discovery. Methanol extracts of P. xanthinum were tested against Gram-negative and Gram-positive bacteria, as well as pathogenic yeast, using the disc diffusion method. The extracts exhibited notable antimicrobial activity, particularly against Escherichia coli (18.6 ± 0.44 mm) and Salmonella enterica serovar Typhi (15.8 ± 0.25 mm). Gas chromatography-mass spectrometry (GC-MS) analysis identified 29 bioactive compounds, evaluated for drug-likeness using Lipinski's rule of five and biological activity predictions. Molecular docking studies with penicillin-binding protein 3 (PBP3) of Pseudomonas aeruginosa (PDB ID: 6I1E) revealed strong binding affinities. Notably, benzenepropanoic acid, ?-(2,5-dioxopyrrolo)-, exhibited a binding energy of -5.9 kcal/mol, while 2,2,3,3-tetramethylcyclopropanoic acid, phenyl ester, showed -5.2 kcal/mol. These findings highlight P. xanthinum as a valuable source of bioactive compounds with potential for combating bacterial resistance. Further investigations into its bioactive mechanisms, pharmacodynamics, and safety profiles are recommended to advance its development as a viable candidate for antimicrobial drug discovery.